Enhancing Web Server Security against Layered Cyber Threats in Healthcare - Rifai, Muhammad Fajar; Hendra, Syaiful; Ngemba, Hajra Rasmita; Azhar, Ryfial; Laila, Rahmah (Advance Sustainable Science, Engineering and Technology, 2024)
Information technology plays an important role in improving operational efficiency at Torabelo Hospital. The server system in use today faces security and optimization challenges. This research analyzes the impact and recommends solutions to improve server security and optimization. The findings show that the server system is vulnerable to various types of attacks and performance degradation. This can negatively impact hospital operations and put patients at risk. The recommended solution is to implement Squid as reverse proxy, WAF (Web Application Firewall), and Snort as IDS (Intrusion Detection System). System testing showed that this solution successfully detected and prevented various common attacks. This research provides insights to health IT professionals to improve the security and performance of their server systems and improve healthcare services to patients at Torabelo Hospital.